THE THE EFFECT OF FINANCIAL PERFORMANCE AND BANKOWNERSHIP ON RETURN ON ASSET IN INDONESIAN BANKING PERIOD 2019-2022 - Wahyudi A C; Abidin Z (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The purpose of this research was analyzed the effect of positively and significantly Operating Expenses on Return on Assets. This research was analyzed the effect of positively and significantly Net Interest Margin on Return on Assets. This research was analyzed the effect of positively and significantly Capital Adequacy Ratio on Return on Assets. This research was analyzed the effect of positively and significantly Loan to Deposit Ratio on Return on Assets. this research was analyzed the effect of positively and significantly Bank Ownership on Return on Assets. Purposive sampling is a sampling technique by determining certain criteria. The sample in this study are commercial banks in Indonesia in the 2019-2022 period except for Islamic Banks, BPD (Regional Development Banks) and Foreign Banks (KCBA, Branch Offices of Foreign Banks). Panel data analysis and hypotheses were tested using Eviews. The results of the study show that bank ownership has the most positive effect on return on assets. Foreign ownership is the percentage of company shares held by foreign investors. Foreign ownership can be an alternative choice when a company wants to control the management. Foreign companies tend to have a good focus on the issue of good corporate governance, so it's the right choice if a company wants to increase the transparency of this aspect.Keyword: Financial Performance, Bank Ownership, Profitability, Banking Company.